2016
DOI: 10.1111/pde.12841
|View full text |Cite
|
Sign up to set email alerts
|

Pachyonychia Congenita: A Spectrum of KRT6a Mutations in Australian Patients

Abstract: This case has unique features. Sharing information can assist patients navigating life with this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Keratin 6A is a family member of type II keratin proteins, biologically KRT6A could lead to epidermalization of squamous epithelium, 6,7 and KRT6A plays an important role in EMT in nasopharyngeal carcinoma, 6 KRT6A mutation plays an important role in pachyonychia congenita and could serve as a diagnosis marker. [7][8][9] In present study, the in vitro KRT6A silencing model was constructed to investigate the biological role of KRT6A. Our data indicate that KRT6A knockdown could significantly undermine the cancer cells proliferation and migration; moreover, KRT6A was involved with CSC transformation and EMT in LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…Keratin 6A is a family member of type II keratin proteins, biologically KRT6A could lead to epidermalization of squamous epithelium, 6,7 and KRT6A plays an important role in EMT in nasopharyngeal carcinoma, 6 KRT6A mutation plays an important role in pachyonychia congenita and could serve as a diagnosis marker. [7][8][9] In present study, the in vitro KRT6A silencing model was constructed to investigate the biological role of KRT6A. Our data indicate that KRT6A knockdown could significantly undermine the cancer cells proliferation and migration; moreover, KRT6A was involved with CSC transformation and EMT in LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that keratin may also function to regulate cell growth and apoptosis as well as protecting cells from impairment and non-mechanical stress (25). Keratin 6A (KRT6A) is a family member of keratin proteins and can lead to epidermalization of squamous epithelium (26,27). KRT6A is a biomarker that is unique to squamous cells (28), while NPC is an undifferentiated squamous cell carcinoma (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…Other frequently reported features of PC‐6a are oral leukokeratosis and palmoplantar blisters, while pilosebaceous/epidermal cysts are predominantly found in PC‐6b or PC‐17 2 . However, our patient rarely showed generalized vesicles/bullae with PC‐6a 2,3 . These atypical manifestations could lead to a misdiagnosis of epidermolysis bullosa.…”
Section: Discussionmentioning
confidence: 59%